Long-Run Impacts of China's WTO Accession on Farm-Nonfarm Income Inequality and Rural Poverty - Ianchovichina, Elena 2000- (The World Bank, 2003)
Many fear China's accession to the World Trade Organization (WTO) will impoverish its rural people by way of greater import competition in its agricultural markets. Anderson, Huang, and Ianchovichina explore that possibility bearing in mind that, even if producer prices of some (land-intensive) farm products fall, prices of other (labor-intensive) farm products could rise. Also, the removal of restrictions on exports of textiles and clothing could boost town and village enterprises, so demand for unskilled labor for nonfarm work in rural areas may grow even if demand for farm labor in aggregate falls. New estimates, from the global economywide numerical simulation model known as GTAP, of the likely changes in agricultural and other product prices as a result of WTO accession are drawn on to examine empirically the factor reward implications of China's WTO accession. The results suggest farm-nonfarm and Western-Eastern income inequality may well rise in China but rural-urban income inequality need not. The authors conclude with some policy suggestions for alleviating any pockets of farm household poverty that may emerge as a result of WTO accession. This paper—a product of the Economic Policy Division, Poverty Reduction and Economic Management Network—is part of a larger effort in the network to assess the impact of China's WTO accession